Estimation of Biomass And Carbon Stock of Aquilaria Microcarpa in Community Forest Plantation of Langkat Regency - Latifah, Siti; Nabila Ismi Mumlahanah Daulay; Grace Rama Novelyta Br Sembiring; Tatasari Cahaya Ningrum (Talenta Publisher, 2025)
Agarwood is a type of non-timber forest product that is well known to communities around the forest and has high economic value. This research aims to determine the amount of biomass per tree in Agarwood plants Aquilaria microcarpa type. Research conducted in Pekan Bahorok Village, Langkat Regency, North Sumatra Province. The method used is purposive sampling by selecting treesAquilaria microcarpa whose body is normal. Biomass estimation uses allometric models from previous researchers, namely Chave, Ketterings, and Basuki. The tree parameters measured were trunk diameter, total height, and tree mass. The biomass estimation results for A. microcarpa aged 8, 10, and 13 years ranged from 3.7 to 25 kg/tree. Meanwhile, the carbon reserves of A. microcarpa range from 1.77 -11.86 kg/tree.